Estresse oxidativo em equinos submetidos à obstrução intraluminal do cólon menor - Bariani Junior, Antonio Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The syndrome colic one of the most important disorders in horses, stand out among its causes obstructive frames, resulting from foreign bodies and or enteroliths located in the lower colon. The development of colic there is reduced local blood flow which follows, when their correction, blood reperfusion. The ischemia followed by reperfusion is the cause of increased postoperative primary degenerative injury. Reperfusion injury can be caused by the production and release of reactive oxygen species (ROS). In view of this, the aim of the present study to analyze molecules resulting from cellular oxidation and antioxidants in serum and lower colonic tissue in horses submitted to experimental intraluminal obstruction of the lower colon. They also evaluated physical parameters heart rate (HR), respiratory rate (RR), rectal temperature (Tr), motility, capillary refill time (TPC), color of mucous membranes, digital pulse and skin turgor. Hematological analysis and leukocytes were made at different times. Analysis of serum for determination of malondialdehyde (MDA) and vitamin E (Vit E), protein product of advanced oxidation (AOPP) (oxidation metabolites), glutathione (GSH) (antioxidant flux), were held at different times: M0 (time before the anesthetic and procedure obstruction), M4 (4 hours, removal of the obstruction), M12, M24, M36, M48, M60 and M72 (corresponding to 12, 24, 36, 48, 60 and 72 hours after occlusion). In the lower colon samples were obtained from M0 (before blocking) after 4 hours of intestinal obstruction (M4) were obtained in the oral region and aboral obstructed. After 72 hours of post surgical (M72) held new collection regions of the lower colon. In these tissue samples were carried out analysis of MDA, AOPP, catalase and GSH. In physiological parameters we observed a significant increase in HR and Tr in M12, and an increase in RR in M24. Hematological evaluation showed a decrease compared to red blood cell count ...

A síndrome cólica um dos distúrbios de maior importância em equinos, a se destacar entre suas causas os quadros obstrutivos, decorrentes de corpos estranhos e ou enterólitos localizados no cólon menor. No desenvolvimento da cólica há diminuição do fluxo sanguíneo local ao qual se segue, quando de sua correção, a reperfusão sanguínea. A isquemia seguida de reperfusão é a causa do aumento da lesão degenerativa principal pós-cirúrgica. As lesões de reperfusão podem ser causadas pela produção e liberação de espécies reativas de oxigênio(EROs). Diante disto, objetivou-se no presente trabalho analisar moléculas decorrentes da oxidação celular e substâncias antioxidantes no soro e no tecido do cólon menor em equinos submetidos experimentalmente a obstrução intraluminal do cólon menor. Também foram avaliados parâmetros físicos frequência cardíaca (FC), frequência respiratória (FR), temperatura retal (Tr), motilidade, tempo de preenchimento capilar (TPC), coloração de mucosas, pulso digital e turgor cutâneo. Análises hematimétricas e leucométricas foram efetuadas em diferentes momentos. Análises no soro para determinação de malondialdeido (MDA), produto protéico de oxidação avançada (AOPP) (metabólitos da oxidação), glutationa (GSH) e vitamina E (Vit. E) (substâncias antioxidantes), foram realizadas em diferentes momentos: M0 (momento antes do procedimento anestésico e precurção da obstrução), M4 (4 horas, retirada da obstrução), M12, M24, M36, M48, M60 e M72 (correspondendo a 12, 24, 36, 48, 60 e 72 horas após a obstrução). No cólon menor foram obtidas amostras em M0 (antes da obstrução), após 4 horas de obstrução intestinal (M4) foram obtidas na região oral, obstruída e aboral. Após 72 horas de pós cirúrgico (M72) realizou-se nova coleta das regiões do cólon menor. Nestas amostras de tecido foram realizadas as analises de MDA, AOPP, GSH e catalase. Nos parâmetros...
Keywords: Cavalo; Glutationa; Vitamina E; Oxidação; Antioxidantes; Equino; Glutathione